# algebra

posted by .

solve for w: the square root of 2-w=w

2-w=w^
w^+w-2
(w+2) (w-10)
w+2=0 w-1=0
w=-2 w=1

• algebra -

√(2-w) = w^2
2-w = w^4
w^4+2w-2 = 0
The solutions to that are not trivial.

So, assuming you meant

√2 - w = w
√2 = 2w
2 = 4w^2
w = ±1/√2

Better try again. Ignoring the first two lines, once you get to

(w+2)(w-10)
I'm sure you meant
(w+2)(w-1) = 0
In which case the roots are indeed -2 and 1

You seriously need to improve you exponential notation!

• algebra -

Wow, that is some creative algebra

√(2-w) = w , or is it √2 - w = w
(notice how my brackets totally change the meaning of the problem)

I will assume the first
square both sides

(√(2-w) )^2 = w^2
2 - w = w^2
w^2 + w - 2 = 0
(w+2)(w-1) = 0
w = -2 or w = 1

Since we squared, both solutions MUST be verified
if x = 1
LS = √(2-1) = 1
RS = 1^2 = 1 = LS
so x = 1

if x = -2
LS = √(2 + 2) = √4 = 2
RS = -2
LS ≠ RS

so the only solution is x = 1

## Similar Questions

1. ### Algebra

Solve 2+ the square root of 4-x=x what is your question?
2. ### algebra

1.)correct 2.)wrong---> the first term is wrong 4(3a^2)^2 = 36a^4 3.) not sure on this one 4.) wrong---> - square root of six is not a solution Hope this Helps! 1)find p(-3)if p(x)=4x^3-5x^2+7x-10 =-184 2)If r(x)=4x^2-3x+7,find …
3. ### algebra

1)Write the expression 9n^6+7n^3-6 in quadratic form,if possible A.9(n^3)^3+7n^3-6 B.9(n^2)^3+7(n^2)-6 C.9(n^3)^2+7(n^3)-6 D.not possible I'm thinking C on this one but im not sure 2)solve b^4+2b^2-24=0 A.-2,-square root of 6,square …
4. ### Pre Algebra

Please help me with some problems. Thank you! Solve the equation by square root property. 3. 2x^2 = 26 I don't understand how to solve this problem. Solve the equation using the quadratic formula. 7. 7x^2=-8x -2 This is what I got …
5. ### Algebra

3(square root of)18 + square root of 2. How would I solve this problem, preferably making the numbers after the square root sign the same?
6. ### Algebra

Use the quadratic formula to solve the equation. Give exact answers: 2x^2 -1 = 6x. The choices are: a) -3 + square root(7)/2, -3 - square root(7)/2 b) 3 + square root(11)/2, 3 - square root(11)/2 c) 3 + square root(7)/2, 3 - square …